Apprendre une langue dans l’interaction verbale - Py, Bernard (My University, 1996)
The articulation of foreign language learning and its actual use in face-to-face communication is a central theme in language teaching studies. If the very existence of this articulation is not questioned, one may however wonder about the discursive and cognitive mecanisms that make it up. This reflexion sheds a particular light on the functioning of verbal interaction involving a teacher and a learner, as well as on the working of learning itself. Besides, it allows an interpretation, which we hope will be original, of some very common teaching behaviours. Finally, it may be an indirect contribution to a more general reflexion on the role of explicite grammar in language learning.